Tamoxifen Citrate- loaded synthetic high-density lipoproteins: Assessment of cellular toxicity in breast cancer cells - Ameerah A. Radhi; Wedad K. Ali; Fitua Al-Saedi (College of Pharmacy / Mustansiriyah University, 2023)
Tamoxifen Citrate (TC) is the standard endocrine therapy for estrogen receptor (ER) positive breast cancer. TC is a selective estrogen receptor modulator (SERM) whose estrogenic properties in uterus have been linked to increased side effects like blood clots, endometrial polyps and cancer. Therefore, significant amount of research has been carried out to develop tamoxifen loaded nano-formulations with a preferential accumulation in tumor tissue rather than healthy tissues. Synthetic high-density lipoproteins (sHDL) are novel nanocarriers with inherent active-targeting ability towards tumor cells through the ligand-receptor interaction between apolipoprotein A-I (Apo A-I) and scavenger receptor class B type I (SR-BI) overexpressed in various malignant cells. The current study was carried out to investigate whether encapsulation of TC in sHDL could improve the cytotoxic effect of TC against malignant cells. For this purpose, the cytotoxicity of TC-sHDL was evaluated in MCF-7 cell line in vitro. MTT assay demonstrated the increased cytotoxicity of TC-sHDL against cancer cells as compared with the cytotoxic effect of the free drug.